Responsividade hepática a substratos gliconeogênicos durante hipoglicemia induzida por insulina (HII) em ratos recém desmamados - Yamashita, Fabiana de Oliveira (2007)
Previous studies from our laboratory have demonstrated an increased hepatic responsiveness to gluconeogenic substrates during insulin induced hypoglycemia (IIH) in adult rats. In this work, we expanded these studies to weaned rats. For this purpose, 12 h food deprived male Wistar rats which received insulin (IIH group) or saline (Control group) were compared. Glycemia was measured 30 min after insulin or saline injection in all animals. Moreover, liver perfusion experiments with saturating concentrations of L-alanine (5 mM), L-glutamine (10 mM), L-lactate (2 mM) and glycerol (2 mM) or combined infusion of these glucose precursors were done to measure hepatic glucose production. In part of the experiments hepatic production of L-lactate and pyruvate were determined. The results demonstrated that IIH increased the hepatic capacity to produce glucose from L-glutamine. The study also shown that the same effect did not occur to L-alanine, glycerol and L-lactate. Thus, we can conclude that the greater hepatic responsiveness to L-glutamine, but not to L-lactate and L-alanine could be attributed to an immaturity of enzymatic systems of hepatic gluconeogenesis in weaned rats, particularly with respect to pyruvate carboxyquinase enzyme. Therefore, we can conclude that L-glutamine could be an important gluconeogenic substrate to promote glucose recovery in weaned rats hypoglicemic.